Cost control methodology (Teplospol company) - Kučerová, Markéta (2013)
The diploma thesis focuses on theoretical and practical aspects of cost control methodology. The effort is to introduce individual tools and methods for cost management. I introduce various instruments for cost management and outline the connections of company costs, systems of their records and their interaction in the form of cost optimization. At the beginning I explain the importance of cost, the reasons for cost management, cost management concepts and their types according to purpose. Then I focus on methodology of costs calculations and budgets as tools for operating cost control. Last section of theoretical part is focused on strategic cost management as a tool for long term cost control. Second part deals with the application of theoretical aspects in practice. This part starts with description of the methodology of cost management in the selected company and also with application of the recommendations resulting from theoretical findings. The main goal of diploma thesis will be achieved by analysing company's current situation, identifying critical problem areas and proposing steps leading to a solution suited for company's needs. The scope of work presented in the first part of the thesis will be applied on Teplospol a.s.; solutions that suit the company will be proposed.